Heart to heart - Hong, Jeremy Xiang Shen (Nanyang Technological University, 2020)
Heart to Heart is Singapore’s first female-centric CPR and AED communication campaign that addresses out-of-hospital cardiac arrest (OHCA), a leading cause of death in Singapore. Targeted at female undergraduates untrained in CPR and AED skills, we aimed to increase their intention to perform bystander support during OHCA incidents. Guided by the Theory of Planned Behaviour (TPB), our pre-campaign research indicated that untrained female undergraduates believed they could not perform bystander support effectively, nor was there a perceived demand for them to perform it. These insights helped shape our strategic pillars - “Teach”, “Talk”, and “Train”. Through these pillars, our campaign highlighted the importance of every individual’s role in the bystander community and allowed them to build their CPR and AED knowledge and skills. This enabled them to be ready to perform bystander support in times of need. The mixed-media tactics used include [1] social media engagement, [2] innovative on-the-ground outreach events, [3] print collaterals, and [4] hands-on CPR and AED training sessions. Our campaign’s reach and impact were evaluated through post-campaign surveys. Campaign exposure resulted in improvements in both the subjective norms and perceived behavioural control constructs of TPB, along with an increase in the intention to perform bystander support. In addition, 97 people from our target audience attended our CPR and AED training sessions. Training was found to play an important role in increasing bystander support readiness. Future campaigns can draw lessons from Heart to Heart and adapt strategies to improve bystander support, particularly for untapped groups like female youth.